Carbon-isotope composition of artiodactyl tooth enamel and its implications for paleodiets - Wang, Bian; Badgley, Catherine (Frontiers in Ecology and Evolution, 2022)
The stable carbon-isotope composition of mammalian tooth enamel is a powerful tool for reconstructing paleodiet and paleoenvironment. Its application in the fossil record relies on a thorough understanding of the isotopic composition of mammalian diets in modern ecosystems. We compiled and evaluated a global dataset of the carbon-isotope values of artiodactyl tooth enamel, supplemented by new samples, for 79 extant species. After correcting for differences in atmospheric carbon-isotope composition, body mass, and digestive physiology, we compared the inferred carbon-isotope values of ingested forage (δ13Cdiet) among seven feeding categories. The artiodactyl herbivore dietary spectrum is expressed through a wide range of δ13Cdiet values, with the most depleted mean value in frugivores and the most enriched in obligate grazers. In general, grazing species have a broader range of isotope values than browsing species, suggesting a wider dietary niche breadth. Notably, variable grazers exhibit a bimodal distribution of δ13Cdiet values, with North American and Asian taxa consuming C3 diets and African taxa consuming C4 diets, reflecting the amount of C4 vegetation in the environment. Variation in δ13Cdiet values also occurs among terrestrial ecoregions and artiodactyl clades. Grassland ecoregions differ significantly from forest ecoregions. We detected a low but significant phylogenetic signal in the mean δ13Cdiet values of extant species, with some of the oldest ruminant lineages having maintained C3 feeding and pure C4 diets being restricted to two bovid clades. Determining variation in δ13Cdiet values in different feeding categories and lineages will help refine paleoecological and paleoenvironmental reconstructions from the rich fossil record of artiodactyls.